Implementación de un banco de pruebas de laboratorio con rotores Savonius que permita la caracterización de curvas de rendimiento (2023)
This project proposed the implementation of a test bench for laboratory with the use of the Savonius rotors that allow the characterization and collection of their yield curves to do tests and adaptations focused on the potential analysis of Eolic resources by the Universidad Antonio Nariño (UAN)’s students from sede Puerto Colombia. Hence, students can strength their acquired knowledge throughout their educational careers.